PENYULUHAN PSIKOLOGI KELAS IBU BALITA DAN ANAK DI POSYANDU DS. BENDO KEC. NOGOSARI KAB. BOYOLALI - Natalina Kristiani (PPM Sdirjianbang Akademi Militer, 2022)
One of the assets of the nation or state is children who are physically and mentally healthy, because it is in their hands that the fate of this nation will be determined. Likewise with the social environment which is a community environment, this community environment has individual interactions with other individuals. So that the state of society will have a certain influence on individual development. Bendo Village, Nogosari District, Boyolali Regency with a population of 60,745. people, where most of their livelihoods are farmers, then the number of toddlers is 82 people and mothers of toddlers are 68 people. Thus, the community really needs an understanding of Posyandu activities and psychological counseling for mothers and toddlers about the importance of understanding children's behavior. This is the background in community service activities in Bendo village, Nogosari sub-district, Boyolali district, Central Java. Results that have been felt by the community; understand child behavior. Children under five years old (toddlers) are a period of formation of the basic human personality, sensing abilities, thinking, language and speaking skills, social behavior and so on. Parents can understand that the most prominent development is motor skills, because motor development is closely related to physical activities.